PROPHYLAXIS OF RICKETS IN PRETERM INFANTS WITH SIGNS OF INTRAUTERINE INFECTION - T.K Znamenskaya; L.I. Shevchenko; O.O. Loshak; I.I. Novik; T.V. Petritsuyk; I.V. Zbrozhyk (Bukovynian State Medical University, 2019)
The article presents the results of fat-soluble form of vitamin D3 (Vigantol) for prevention of rickets in preterm infants with intrauterine infection from mothers with bacterial-viral mixt-infection. The data obtained have shown that use of the drug Vigantol promotes effective and save prevention of rickets in preterm infants with evidence of intrauterine infection compared to water-soluble forms.